Exploring Geometric Concepts in the Medan Post Office through an Ethnomathematical Approach - May Sharah Athifah; Tanti Jumaisyaroh (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Geometry is often considered abstract and difficult to understand because it is rarely linked to real life and the surrounding culture. Therefore, a learning innovation is needed using the Medan Post Office. A culturally acculturated colonial heritage building studied in depth from an ethnomathematical perspective. This study aims to explore the cultural values ​​and geometric concepts inherent in the architecture of the Medan Post Office using an ethnomathematical approach. It employs a qualitative ethnographic design, utilizing primary data from observations and interviews alongside secondary data from relevant literature; data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal concepts of plane geometry (rectangles, squares, circles, semicircles, octagons, right-angled trapezoids, and isosceles triangles) and spatial geometry (pyramids, prisms, rectangular prisms, and cubes). The building embodies ethnomathematical elements resulting from the acculturation of local culture with colonial architecture, socio-historical functions, and environmental adaptation. This research enriches the study of cultural heritage ethnomathematics and offers potential as a resource for contextual, culture-based mathematics learning.